A new sound insulation lightweight concrete masonry block. Design and experimental characterization - Hipólito Sousa (2004)
The purpose of this paper is to present an innovative design approach for a sound insulation lightweight concrete masonry unit made with expanded clay LECAÒ. This block is especially developed and suited for sound insulation between dwellings and presents an airborne sound insulation that allows realizing separating walls between different houses quicker and with lower costs. In the design phases different walls solutions and block geometry have been studied and tested to define the optimum solution. After the stabilization of the unit masonry geometry, a deep characterization of block and final walls has been made. The experimental work includes acoustical, physical and mechanical properties of the blocks and walls. A synthesis of this work is presented.